The Role of Finerenone in Diabetic Nephropathy - Inês Pereira Guerra (2022)
Chronic kidney disease (CKD) is a clinical syndrome characterized by a deterioration of the glomerular filtration rate (GFR) and/or kidney damage, documented for a period of at least 3 months. Diabetes Mellitus (DM) has emerged as its leading cause, given its high and increasing prevalence worldwide. Patients with diabetic nephropathy are at increased risk of developing cardiovascular complications. Numerous etiologies for disease progression are described, but it is crucial to highlight the role of the renin-angiotensin-aldosterone system (RAAS) and the mineralocorticoid receptor (MR). Based on this, it was thought that the combination of both therapies would lead to the inhibition of chronic kidney disease progression. However, given the high risk of hyperkalemia, this is not an effective alternative. In this regard, finerenone, a non-steroidal antagonist of the mineralocorticoid receptor, which appears to mitigate the adverse effects of steroid antagonists, has emerged. To prepare this review, articles were selected, through a PubMed search, with the terms "Chronic Kidney Disease", "Diabetes Mellitus" and "Finerenone". The search was narrowed down to articles written in English and published within the last 10 years. Frequently cited articles from the area, not selected from the initial search, were also added. The results seem to indicate finerenone as a drug that can halt the progression of kidney disease and decrease cardiovascular morbidity and mortality, in diabetic patients, without significantly increasing the risk of hyperkalemia. However, more scientific evidence is needed, regarding its efficacy and safety, as well as the extrapolation of its results to patients with non-diabetic chronic kidney disease, or diabetic patients who have not yet developed kidney disease.